On Becoming and Vanishing of Museum Objects (KULT_online, 2017)
The edited volume Die Logik des Museums. Beiträge zur Museologie by Roger Fayet deals with exhibitions in art and history museums as a multi-layered phenomenon. Focusing on theoretical discussions of the practical aspects of the curatorial business, Fayet analyzes modes of collecting and discarding museum objects. The attribution of meaning based on the communicational ambiguity of objects as well as on their mode of positioning refers to the possible interpretations of exhibitions. Fayet elaborates and comments on the debates tied to the discarding of museum objects and the comprehensibility of authorship within the museum context. He argues against the removal of objects from museum collections and is therefore critical of their collecting concepts.